2016
DOI: 10.1002/adsc.201600795
|View full text |Cite
|
Sign up to set email alerts
|

By‐Product‐Catalyzed Redox‐Neutral Sulfenylation/Deiodination/Aromatization of Cyclic Alkenyl Iodides with Sulfonyl Hydrazides

Abstract: A by‐product‐catalyzed redox‐neutral process has been established through tandem sulfenylation/deiodination/aromatization of cyclic alkenyl iodides with sulfonyl hydrazides. In the absence of external catalysts and additives a range of 4‐iodo‐1,2‐dihydronaphthalenes reacted with sulfonyl hydrazides to give structurally diverse 2‐naphthyl thioethers in good yields. Mechanistic studies showed that at an early stage sulfonyl hydrazides decomposed completely to thiosulfonates and disulfides and at a late stage the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…On the basis of literature reports, and our above observations in the present work, a plausible reaction mechanism is proposed (Scheme ). In the presence of water, 2a disassociate into a sulfur anion and PhS + ( A ).…”
Section: Resultssupporting
confidence: 57%
“…On the basis of literature reports, and our above observations in the present work, a plausible reaction mechanism is proposed (Scheme ). In the presence of water, 2a disassociate into a sulfur anion and PhS + ( A ).…”
Section: Resultssupporting
confidence: 57%
“…Despite the wide applications of by‐products as a catalyst, additive, or reagent in tandem reactions, by‐product dimethyl sulfide generated from the oxidative bromination reaction of YBr/DMSO was generally disposed as toxic and smelly waste. With our continuous interest in regioselective halogenation and hydrogen chemistry, herein, we wish to report a mild and regioselective bromination of phenols with TMSBr (Scheme C).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Tian and co-workers 80 reported a redox-neutral process via tandem thiolation/deiodination/aromatization of cyclic alkenyl iodides with sulfonyl hydrazides (Scheme 32). Mechanistic studies showed that molecule iodine, as a byproduct, was generated from dihydronaphthalene iodide 50a upon heating and served as a catalyst for the decomposition of sulfonyl hydrazide and subsequent formation of 2naphthyl sulfide 50.…”
Section: Alternative Reductantsmentioning
confidence: 99%